Edukasi Pasar Modal Pada Guru-Guru SD N 035 Tarai Bangun - Maswir, Mulyadi; Syahsudarmi, Siti; Asnahwati (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
Low financial literacy among educators often acts as an obstacle to achieving long-term financial well-being. This Community Service (PKM) activity aims to enhance the literacy and understanding of teachers at SD N 035 Tarai Bangun, Kampar Regency, Riau, regarding capital market instruments, particularly stock investments. The primary problem faced by the partners was the negative stigma that capital market investment is reserved only for the upper economic class, as well as a lack of technical knowledge regarding legal stock trading mechanisms on the Indonesia Stock Exchange (IDX). The methods used in this activity included lectures, interactive discussions, and evaluations through pre-test and post-test instruments. This activity also invited expert speakers from the Indonesia Stock Exchange (IDX) and KISI to provide validated information. The results showed a significant increase in the participants' knowledge and understanding aspects. Before the education, the majority of participants did not understand capital market concepts; however, after the activity, all participants (100%) were able to identify capital market instruments and understand the mechanics of stock ownership. Although cognitive understanding has improved, the teachers still require further practical depth through the Capital Market School (SPM) program to begin transacting independently. In conclusion, this education successfully dismantled the participants' psychological barriers toward investment and is expected to encourage the emergence of new investors among educators to achieve financial independence.